Business intelligence as a supportive mechanism for strategic flexibility A quantitative study of a sample of commercial banks in the wilaya of El-Oued - Aichouche, Aouatef (Dirassat Journal Economic Issue, 2023)
This study aimed to highlight the necessity of Dependence on Business intelligence in order to reach strategic flexibility, by dropping the field study on some commercial banks in El-Wadi State, depending case study technique using the questionnaire as a tool to gather information, It was distributed to 45 managers, and the number of retrieved questionnaires valid for statistical analysis was 37 questionnaires, Several statistical methods are used in the statistical analysis of the information, have used SPSS. The study concluded that there is a positive, statistically significant relationship with business intelligence in supporting strategic flexibility.